Studying the role of GCLC gene polymorphisms in predicting the clinical course of acute alcoholic pancreatitis - T. A. Samgina (Бюллетень сибирской медицины)
The aim of the study was to evaluate the role of polymorphic loci rs12524494, rs17883901, rs606548, rs636933, rs648595, and rs761142 in the GCLC gene in predicting the clinical course of acute alcoholic pancreatitis (AAP).Materials and methods. The material of the study was blood DNA samples obtained from 547 patients with AAP and 573 healthy individuals. The average age of patients was 48.9 ± 13.1 years, the average age of healthy individuals was 47.8 ± 12.1 years. Genotyping was performed using the MassARRAY 4 Analyzer. Plasma levels of total glutathione were determined using the OxiSelect™ Total Glutathione (GSSG/GSH) Assay Kit STA-312. The level of reactive oxygen species (ROS) was determined using the OxiSelect™ In Vitro ROS/RNS Assay Kit (Green Fluorescence) STA-347 (Cell Biolabs Inc., USA). The kinetic colorimetric assay was used to determine the level of amylase in the blood serum. Statistical data processing was performed using the Statistica 10.0 and SNPStats software.Results. It was found that the polymorphic loci rs606548 (genotype C/C, odds ratio (OR) = 3.34, 95% confidence interval (CI) 1.29–8.66, р = 0.007), rs648595 (genotype G/T, OR = 1.56, 95% CI 1.04–2.36, р = 0.029), andrs12524494 (genotype A/G, р = 0.021) in the GCLC gene were predictors of an increased risk of necrotizing pancreatitis. For the genotype T/T of rs648595 (recessive model) in the GCLC gene, the lowest values of oxidized glutathione were found, whereas rs17883901 – G/A in the GCLC gene was associated with the highest ROS values in the blood. The rs761142 A/A genotype in the GCLC gene (OR = 1.70, 95% CI 1.12–2.59; р = 0.010) showed predisposition to acute peripancreatic fluid сollection, and the rs648595 G allele (OR = 1.47, 95% CI 1.01–2.13; р = 0.042) in the GCLC gene exhibited predisposition to the formation of acute pancreatic pseudocysts. Predisposition to massive bleeding was associated with rs17883901 (G/A genotype, OR = 6.20, 95%CI 1.3–28.81; р = 0.031) in the GCLC gene.Conclusion. The established genotype – phenotype associations will make it possible to predict the clinical course of AAP in a particular patient, taking into account their genetic makeup, as well as to determine the treatment strategy in a timely manner.